Concurrent validity of the alcohol purchase task in relation to alcohol involvement: protocol for a systematic review and meta-analysis. Issue 6 (28th June 2020) - González-Roz, Alba; Martínez-Loredo, Víctor; Secades-Villa, Roberto; Amlung, Michael; MacKillop, James
Abstract : Introduction: Alcohol demand, as measured by an alcohol purchase task (APT), provides a multidimensional assessment of the relative reinforcing efficacy of alcohol. The objective of this meta-analysis is to critically appraise the existing literature on the concurrent validity of the APT by meta-analysing the cross-sectional relationships between indices of the APT (ie, breakpoint, Omax, Pmax, elasticity and intensity) and alcohol-related measures. It also aims to examine methodological procedures used to obtain APT indices and individual variables as potential moderators on the assessed estimations. Methods and analysis: A comprehensive literature search conducted from inception to April 2020 will be conducted in the PubMed, PsycINFO, Web of Science and Scopus databases. Two authors will independently screen and extract data from articles using a predefined protocol search and extraction forms. Disagreements will be resolved through discussion with two additional reviewers. All results will be tabulated, and a random-effect meta-analysis will be conducted. Participants' sex, number of prices and APT methodological procedures will be examined as potential moderators on the observed effect sizes. Ethics and dissemination: Results of this meta-analysis will characterise the concurrent validity of the APT in the existing literature. Further, the results are anticipated to provide evidence on which index (or indices) is most robustly associated with alcohol use and severity. Ethics approval was not required for this study and the results will be published in a peer-reviewed journal. PROSPERO registration number: CRD42019137512